EDUCATION OF SPECIFIC PHYSICAL FITNESS AND SPEED OF THE WRESTLER - Akhtamov Jamshed Bahromovich (Journals Park Publishing, 2023)
In this article training of national wrestlers , development of agility and strength qualities , effective formation of sports skills as the most important foundation in training of wrestlers , exercises related to flexibility development , physical training, development of special action skills issues were discussed.
Keywords: complex movement skills, physical training, young wrestlers, possibility of development, necessary factors, used methods, development, stretching, bending, spreading, compression, twisting of joints, special importance.